2020
DOI: 10.1088/2057-1976/ab7bc6
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing MR Imaging isocenter variation in MRgRT

Abstract: We characterized MRI isocenter variation at various gantry positions in two 0.35 T MRgRT systems using two independent methods. First, image center-based quantification was employed on 3D volumetric and 2D cine images of a 24 cm diameter spherical phantom at various gantry positions in the MRI QA mode. The center of the phantom images was identified to quantify the variation of the imaging center at each gantry position. Second, image registration-based quantification was used in radiotherapy mode. 3D volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…The ADC values produced by the 0.35 T system in this study were also significantly lower than those produced on 1.5 T and 3.0 T systems. Additionally, geometric distortion assessment using fiducial markers showed a gantry dependent distortion, similar to those reported by Kim et al 19 . for anatomical imaging sequences used during patient treatment on the MR‐LINAC system.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The ADC values produced by the 0.35 T system in this study were also significantly lower than those produced on 1.5 T and 3.0 T systems. Additionally, geometric distortion assessment using fiducial markers showed a gantry dependent distortion, similar to those reported by Kim et al 19 . for anatomical imaging sequences used during patient treatment on the MR‐LINAC system.…”
Section: Discussionsupporting
confidence: 84%
“…An added challenge presented by the MR‐LINAC system is the motion of the LINAC gantry around the MRI. Although there is significant magnetic and RF shielding between the MRI and LINAC subsystems, changes in the gantry angle cause changes in the imaging isocenter and spatial integrity 19 . These changes could adversely impact the accuracy of ADC values and reduce their utility for ART or disease monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Gantry angle‐dependent shifts in the imaging isocenter were reported on a 0.35‐T MRI‐Linac system. A maximum displacement of 1.8 mm for 3D true fast imaging with (balanced) steady‐state precession (TrueFISP) scans used for treatment planning and patient setup was measured 7 . A maximum displacement of 0.9 mm for 2D cine TrueFISP used in real‐time treatment delivery and beam gating was also observed 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Many components of the LINAC and beam delivery systems have the potential to further reduce the accuracy of the integrated MRI system. The impact of gantry position on radiation‐MR isocenter coincidence has been investigated on MR‐ 60 Co and MR‐LINAC systems, and shown variations in the MR isocenter depending on gantry position 15,16 . Utilizing an MLC for beam shaping introduces mobile metallic material, which is often the RT component closest to the magnet, that may also impact the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of gantry position on radiation-MR isocenter coincidence has been investigated on MR- 60 Co and MR-LINAC systems, and shown variations in the MR isocenter depending on gantry position. 15,16 Utilizing an MLC for beam shaping introduces mobile metallic material, which is often the RT component closest to the magnet, that may also impact the magnetic field. A computational study by Kolling et al investigated MLC impact on field homogeneity including source-to-isocenter distance, field size, magnetic field strength, and other properties and found that MLC field size caused dynamic changes in field distribution.…”
mentioning
confidence: 99%